(untitled) (International Journal of Food and Nutritional Sciences, 2022)
However hair does not assist any critical physiological condition in human beings but it plays significant role in our social and mental life. Androgenic baldness and circular/spot baldness these are the most conventional type of hair loss.In market most of the synthetic active ingredients are available for the treatment of hair loss still with some limitation. These synthetic compounds are effective but having some side effect. From the classical times in Ayurveda, Unani and Chinese approaches medicinal plants have been generally used for hair growth promotionso that the herbal medicines gaining popularity day by day because they are safer and effective from synthetic. This review article discusses the mechanism of the herbal drug with their phyto-constituents with emphasis in the hair growth promotion activity. It also gives knowledge aboutdifferent herbs and herbal formulation with their action. So the aim of the present article is to be giving a cumulative knowledge about the hair loss treatment with emphasis on the hair loss cause and type focused on the herbal hair formulation with scientific validation with herbal and synthetic drug or isolated compound for hair growth potential activity.The knowledge condensed in the papermay be an vision to designa new preparations for the treatment of hair loss.